Intimate partner violence and suicidal indicators in the Sierra of Peru: a transversal study about sociodemographic factors - Rodriguez-Poma, Kattya L. (2025)
Objective: To evaluate the association between suicidal indicators and intimate partner violence, and characterize the related sociodemographic factors in women of 18 years or older, in the cities of Abancay, Ayacucho, Cajamarca, Huaraz and Puno. Methodology: Analytical and probabilistic cross-sectional study, using data from a secondary source obtained from the Epidemiological Studies of Mental Health of Sierra cities in the years 2016, 2017 and 2018, in a sample of 6176 women. Results: A significant association was found between intimate partner violence and suicidal indicators (aOR: 3.16; CI: 2.50–3.99). The victims of psychological violence had a higher risk of presenting any suicidal indicator (aOR: 3.2; CI: 2.53-4.06), with the most likely to occur being suicidal planning (aOR: 17.12; CI: 6.13-47.81). The sociodemographic factor most frequently was the level of extreme poverty (aOR: 2.4; CI: 1.01-5.78). Conclusions: In the clinical evaluation of women victims of intimate partner’s violence, the presence of suicidal indicators, mainly suicidal planning, must be considered. This search should be prioritized if the woman lives in a situation of extreme poverty.